1997
DOI: 10.3109/10428199709058308
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Human ALL-1/MLL/HRX Gene

Abstract: The human ALL-1/MLL/HRX gene on chromosome 11q23 is the site of many locally clustered chromosomal alterations associated with several types of acute leukemias, including deletions. partial duplications and reciprocal translocations. Structurally variant proteins derived from an altered ALL-1 gene presumably make essential contributions to the malignant transformation of hematopoietic progenitor cells. The ALL-1 gene is spread over approximately 92 kb and consists of at least 37 exons. An exon/intron map inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…Breakpoints from patients (circled numbers or letters) were analysed as described in the text and are connected by lines between both breakpoint cluster regions. Numbering of exons of the MLL gene according to Nilson et al (1996) and Marschalek et al (1997); of the AF-4 gene according to Nilson et al (1997) cross-over mechanism could have produced the observed ®nal state. Each of these translocation events was accompanied by deletions, duplications and/or inversions of germline DNA sequences.…”
Section: Characteristic Duplications Deletions and Inversions Are Prmentioning
confidence: 99%
See 3 more Smart Citations
“…Breakpoints from patients (circled numbers or letters) were analysed as described in the text and are connected by lines between both breakpoint cluster regions. Numbering of exons of the MLL gene according to Nilson et al (1996) and Marschalek et al (1997); of the AF-4 gene according to Nilson et al (1997) cross-over mechanism could have produced the observed ®nal state. Each of these translocation events was accompanied by deletions, duplications and/or inversions of germline DNA sequences.…”
Section: Characteristic Duplications Deletions and Inversions Are Prmentioning
confidence: 99%
“…The MLL/AF-4 mRNA of patient PCB contained a fusion of MLL exon 11 to AF-4 exon 4 (nomenclature according Nilson et al, 1996Nilson et al, , 1997Marschalek et al, 1997). The AF-4/MLL mRNA of the same patient showed a fusion of AF-4 exon 3 to MLL exon 12.…”
Section: Mapping Of Both Translocation Breakpoints For Three Additionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other MLL rearrangements previously studied, no extra nucleotides or heptamer-like signals were observed at the junction point, which probably rules out any involvement of VDJ recombinase. It has been shown that large numbers of ALU sequences are present at the MLL breakpoint (Marschalek et al, 1997), which may render this region particularly prone to recombination events. An ALU sequence was found on chromosome 15 660 bp downstream from the breakpoint, which could thus be predisposed to translocation events.…”
mentioning
confidence: 99%